Pengaruh daya tarik iklan di sosial media Instagram terhadap minat beli konsumen produk Innisfree - Piyoh, Dea Dela; Annahli, Yuliarti Maghfira; Gaffar, Vanessa (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Consumers have a tendency to develop an intention to buy a product after seeing product advertisements in various electronic media, one of which is through Instagram social media. This study aims to determine whether there is an effect of advertising attractiveness on Instagram social media on consumer buying interest in Innisfree products. The method used in this research is an explanatory survey with a quantitative approach. Data collection is done by distributing questionnaires / questionnaires to respondents which consist of several statements. The population in this study were consumers of Innisfree products with a sample of 100 respondents. The sampling technique used is simple random sampling. The data analysis technique used is descriptive and inferential analysis which is processed using the Partial Least Square (PLS) 4.0 analysis tool. The results showed that there was a positive and significant influence of the Advertising variable on consumer buying interest. This research is expected to provide a number of theoretical and practical guidelines on how entrepreneurs can effectively implement advertisements on the Instagram social media platform to attract consumer buying interest.